Macrophage Polarization in Leprosy–HIV Co-infected Patients - da Silva, Tatiana Pereira; Bittencourt, Tamiris Lameira; de Oliveira, Ariane Leite; Prata, Rhana Berto da Silva; Menezes, Vinicius; Ferreira, Helen; Nery, José Augusto da Costa; de Oliveira, Eliane Barbosa; Sperandio da Silva, Gilberto Marcelo; Sarno, Euzenir Nunes; Pinheiro, Roberta Olmo (Frontiers in Immunology, 2020)
In HIV-infected individuals a paradoxical clinical deterioration may occur in pre-existing leprosy when highly active antiretroviral therapy (HAART)-associated reversal reaction (RR) develops.Leprosy-HIV patients during HAART may present a more severe form of the disease (RR/HIV) but the immune mechanisms related to the pathogenesis of leprosy-HIV co-infection remain unknown. Although the adaptive immune responses have been extensively studied in leprosy-HIV - individuals, recent studies have described that innate immune cells may drive the overall immune responses to mycobacterial antigens. Monocytes are critical to the innate immune system and play an important role in several inflammatory conditions associated with chronic infections. In leprosy, different tissue macrophage phenotypes have been associated with the different clinical forms of the disease, but it is not clear how HIV infection modulates the phenotype of innate immune cells (monocytes or macrophages) during leprosy. In the present study, we investigated the phenotype of monocytes and macrophages in leprosy-HIV individuals, with or without RR. We did not observe differences between the monocyte profiles in the studied groups; however, analysis of cell phenotype in skin cells revealed that RR/HIV group presents a higher expression of MRS1, CD209, VEGF, ARG2, and PPARG when compared with the RR group. Our data suggest that different phenotypes of tissue macrophages found in the skin from RR and RR/HIV patients could differentially contribute to the progression of leprosy.